Development of an Immortalized Porcine Fibroblast Cell Panel With Different Swine Leukocyte Antigen Genotypes - Le, Quy Van Chanh; Youk, SeungYeon; Choi, Munjeong; Jeon, Hyoim; Kim, Won-Il; Ho, Chak-Sum; Park, Chankyu (Frontiers in Genetics, 2022)
Immortalized cell lines are valuable resources to expand the molecular characterization of major histocompatibility complex genes and their presented antigens. We generated a panel of immortalized cell lines by transfecting human telomerase reverse transcriptase (hTERT) into primary fibroblast cells prepared from ear, fetal, and lung tissues of 10 pigs from five breeds and successfully cultured them for 30-45 passages. The cell growth characteristic of the immortalized fibroblasts was similar to that of primary fibroblast, which was unable to form colonies on soft agar. The genotypes of major swine leukocyte antigen (SLA) genes, including three classical class I (SLA-1, -2, and -3) and three class II genes (DQB1, DRB1, and DQA), were determined using high-resolution typing. A total of 58 alleles, including a novel allele for SLA-2, were identified. Each cell line was unique. A cell line derived from a National Institutes of Health miniature pig was homozygous across the six major SLA genes. The expression levels of SLA classical class I genes varied among the cell lines and were slightly upregulated in the immortalized compared to the primary cells based on semiquantitative reverse transcription polymerase chain reaction. The immortalized porcine fibroblast cell lines with diverse SLA haplotypes that were developed in this study have potential to be applied in studies regarding the molecular characteristics and genetic structure of SLA genes and epitope–major histocompatibility complex interactions in pigs.